1976
DOI: 10.6028/nbs.ir.75-925
|View full text |Cite
|
Sign up to set email alerts
|

Final summary report study of the National Measurement System 1972-75

Abstract: article in Science , emphasized the basis for a systems viewpoint in interrelated measurements activities and the idea has continued to evolve. Today, we think of the U.S. National Measurement System in terms of all the intellectual, functional and institutional activities which enter into measurements throughout our society. Moreover, we seek to understand more completely the structural nature of this system and its architectural needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…There was also a massive expansion in expenditure on measurement related activities. Studies conducted by NBS (9,11,12,14,17) between 1967 and 1984 indicated that the expenditure on measurement by industry, government and the community was between 3 and 6% of GNP and sectoral measurement intensity i.e. the expenditure on measurement related activities as a percentage of total expenditure varied between 20% and less than 1% of sector expenditure.…”
Section: The National Measurement Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…There was also a massive expansion in expenditure on measurement related activities. Studies conducted by NBS (9,11,12,14,17) between 1967 and 1984 indicated that the expenditure on measurement by industry, government and the community was between 3 and 6% of GNP and sectoral measurement intensity i.e. the expenditure on measurement related activities as a percentage of total expenditure varied between 20% and less than 1% of sector expenditure.…”
Section: The National Measurement Systemmentioning
confidence: 99%
“…In 1967 a paper by Huntoon (9) put forward the Concept of a National Measurement System and the concept was further developed at NBS in the early 1970's (9,11,12) and was defined as comprising (11) "All of the activities and mechanisms-intellectual, operational, technical and institutional -used by the country to produce the physical measurement data needed to create the objective, quantitative knowledge required by our society. This knowledge is used to describe, predict, communicate, control and react in many aspects of our personal and social lives, science and technology.…”
Section: The National Measurement Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a macroeconomic study was performed of measurements in our economy [327,173,200,218]. The overall design and specific findings of the study have been presented in a Final Surmiary Report [307].…”
Section: Cernsmentioning
confidence: 99%
“…It is a significant consumer of economic resources. It generates essential economic benefits [307,327].…”
Section: Economic Considerationsmentioning
confidence: 99%